2022
DOI: 10.1590/s2237-96222022000200002
|View full text |Cite
|
Sign up to set email alerts
|

Descrição das notificações de atendimento antirrábico humano para profilaxia pós-exposição no Brasil, 2014-2019

Abstract: Resumo Objetivo: Analisar os atendimentos antirrábicos humanos de profilaxia pós-exposição no Brasil. Métodos: Estudo descritivo utilizando dados do Sistema de Informação de Agravos de Notificação no Brasil, de 2014 a 2019. Resultados: Foram notificados 4.033.098 atendimentos antirrábicos, com média de 672.183 ao ano. Houve maior percentual de atendimentos em pessoas do sexo masculino (n = 2.111.369; 52,4%), menores de 19 anos de idade (n = 1.423.433; 35,3%), residentes em área urbana (n = 3.386.589; 88,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 11 publications
(38 reference statements)
5
8
0
Order By: Relevance
“…The incidence of aggression was similar between the sexes, with a predominance in males; the highest frequency was in the age group between 20 and 39 years, and was more prevalent in white people ( Table 1 ). The characteristics of the victims were similar to those reported in other studies 2 , 4 , 5 , 9 , 11 ; however, a higher frequency of female victims 12 was observed in RJ.…”
supporting
confidence: 87%
See 4 more Smart Citations
“…The incidence of aggression was similar between the sexes, with a predominance in males; the highest frequency was in the age group between 20 and 39 years, and was more prevalent in white people ( Table 1 ). The characteristics of the victims were similar to those reported in other studies 2 , 4 , 5 , 9 , 11 ; however, a higher frequency of female victims 12 was observed in RJ.…”
supporting
confidence: 87%
“…Regarding education, the highest percentage of occurrences was observed in individuals with elementary school education at the time of aggression ( Table 1 ), similar to data reported in Brazil (34.5%), where most of the occurrences were reported in individuals with complete elementary school education 2 . This predominance is possibly associated with the fact that lower-level education is more frequent among poorer individuals and, consequently, the dog is welcomed at home, not only as a pet but also to help protect the residence.…”
supporting
confidence: 82%
See 3 more Smart Citations